Comparison of quick point of care test for paediatric small bowel hypolactasia with biochemical lactase assay. (29th September 2015) - Rao, P; Jordinson, M; Reed, C; Campbell, D
Abstract : Background: The usefulness of a new quick test for endoscopic diagnosis of paediatric-type hypolactasia was tested in duodenal biopsies. In this test, an endoscopic biopsy from the postbulbar duodenum is incubated with lactose on a test plate, and a colour reaction develops within 20 min as a result of hydrolysed lactose (a positive result) in patients with normolactasia, whereas no reaction (a negative result) develops in patients with severe hypolactasia. Aims: The aim of this study was to compare the Biohit lactose intolerance quick (BLIQ) test to the "gold standard" biochemical duodenal lactase (DL) activity assay in the paediatric population. Patients and Methods: Two postbulbar duodenal biopsies were taken from 38 prospective children (0–16 years) who underwent upper GI endoscopy over a period of 1 year (June 2008–May 2009) at a single tertiary paediatric gastroenterology unit. The biopsies were used for the quick lactase test (Biohit PLC, Helsinki, Finland) and in biochemical disaccharidase (lactase, trehalase, sucrase, and maltase) assays. Results: 38 children (19 male) of median age 5.45 years (0.3–14.8 years) had the combined testing. The authors further subdivided this group into those children that had their biopsies with a larger endoscope (XQ, n=26) and thus a bigger biopsy forceps and those children that had a smaller endoscope (XP, n=12) and thus a smaller biopsy forceps. The results are tabulated below. Conclusion: The quick lactase test effectively identifies children with severe duodenal hypolactasia. These results are based on small numbers but tend to support findings in adult studies. The sensitivity and negative predictive value of the BLIQ was 100% on comparing it to DL. The specificity too appears to be high but variable (86% in XQ and 80% in XP groups). This would suggest a lower specificity perhaps, secondary to smaller size of the biopsies obtained and may warrant the need for two biopsies. In comparison with biochemical lactase assays, the sensitivity and specificity of BLIQ for indicating hypolactasia is very high and appears to be an effective point of care test for paediatric hypolactasia.